Impact of External and Internal Factors Consumer has on Purchase Intention Live Streaming Shopping - Jocelyn, Nathania; Christiarini, Renny (Universitas Yudharta Pasuruan, 2025)
Introduction; This research explores the factors influencing purchase intention through live streaming shopping in the fashion sector on social commerce platforms in Batam City. With the rising popularity of online shopping through interactive streaming channels, it is essential to understand the key determinants of consumer purchasing behavior in this context. The research model integrates constructs of interactivity, informativeness, professionalism, attitude, and impulsiveness as potential predictors of purchase intention, with trust serving as a mediator. Methods; Data was collected through an online survey of active live streaming shopping users in Batam. Measurement metrics utilized a 5-point Likert scale to assess these variables. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Results; The analysis results reveal that interactivity, professionalism, and attitude have a significant positive impact on both trust and purchase intention. Informativeness positively influences trust but does not significantly affect purchase intention, while impulse buying positively affects purchase intention without influencing trust. Conclusion; Trust plays a strong mediating role in the relationships between interactivity, professionalism, attitude, and informativeness with purchase intention, except for impulse buying. These findings provide valuable insights for marketers in designing more effective marketing strategies through live streaming channels and are expected to enhance understanding of consumer shopping behavior.